2022
DOI: 10.1021/acs.inorgchem.1c03108
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Ni(0) Decomposition: Mechanistic Insights into AgF-Assisted Nickel-Mediated Silylation

Abstract: In nickel-mediated Kumada cross-coupling reactions, low valent active nickel complexes are often generated in situ and the ligands usually govern the reactivity or stability of these complexes. However, the decomposition of active nickel complexes is inevitable if the subsequent reaction is sluggish. While we recently developed AgF-assisted nickel catalysis to cross-couple methyl ethers and silylmagnesium reagents, the intriguing catalytic role of AgF and the actual active nickel species remains elusive. Recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Anionic nickelates derived from silyl anions have more recently been implicated in the enantiospecific silylation of benzyl methyl ethers. 56 57 31 P NMR spectroscopy studies support that an Ni(0)-ate complex of the constitution [L n Ni–SiMe 3 ] – [MgI(solv)] + is formed on addition of Me 3 SiMgI(TMEDA) to NiBr 2 (diglyme)/PCy 3 , or by direct treatment of the Ni(0) precursor, Ni(PCy 3 ) 2 , with Me 3 SiMgI(TMEDA). This same signal is also observed in the reaction mixture, and cyclic voltammetry and UV-Vis spectroscopy studies suggest that this Ni(0)-ate is the predominant resting state.…”
Section: Anionic Nickelatesmentioning
confidence: 91%
“…Anionic nickelates derived from silyl anions have more recently been implicated in the enantiospecific silylation of benzyl methyl ethers. 56 57 31 P NMR spectroscopy studies support that an Ni(0)-ate complex of the constitution [L n Ni–SiMe 3 ] – [MgI(solv)] + is formed on addition of Me 3 SiMgI(TMEDA) to NiBr 2 (diglyme)/PCy 3 , or by direct treatment of the Ni(0) precursor, Ni(PCy 3 ) 2 , with Me 3 SiMgI(TMEDA). This same signal is also observed in the reaction mixture, and cyclic voltammetry and UV-Vis spectroscopy studies suggest that this Ni(0)-ate is the predominant resting state.…”
Section: Anionic Nickelatesmentioning
confidence: 91%
“…Rasappan and co-workers proposed catalyst decomposition to metallic nickel as a problematic pathway for efficient catalysis in a nickel-mediated Kumada coupling of ethers with silylmagnesium halides. 12,13 The nucleation of reduced metal species can proceed through slow multimetallic nanocluster formation followed by autocatalytic surface growth. 14 The rate of multimetallic nucleation events can be decreased by decreasing the concentration of reduced homogeneous metal species.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The observation of black particles suggested that catalyst decomposition to form nickel black may have inhibited product formation. Rasappan and co-workers proposed catalyst decomposition to metallic nickel as a problematic pathway for efficient catalysis in a nickel-mediated Kumada coupling of ethers with silylmagnesium halides. , The nucleation of reduced metal species can proceed through slow multimetallic nanocluster formation followed by autocatalytic surface growth . The rate of multimetallic nucleation events can be decreased by decreasing the concentration of reduced homogeneous metal species. , Decreasing the catalyst loading to 10 mol % and running the reaction at 120 °C resulted in a 1a / 2a area ratio of 9/91 (Table , entry 5).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, a systematic study is required on distinguishing the radical chain reaction from sequential reduction, identify the active nickel species and the actual reductant. As part of our ongoing study on nickel‐mediated cross‐coupling reactions [15,17] and mechanistic investigations, [17b] we present here our experimental and spectroscopy‐based mechanistic studies, including NMR, UV, and CV. Our finding reveals the active Ni(I) species, a radical chain mechanism, a synergistic reduction of pyridinium salts by Ni(I) and Mn, the rate‐limiting reductive alkylation and the resting state Ni(II) species.…”
Section: Introductionmentioning
confidence: 99%